The Austerity State - Evans, Bryan M., 1960-; McBride, Stephen (Book collections on Project MUSE., 2017)
"This volume focuses on the state's role in managing the fall-out from the global economic and financial crisis since 2008. For a brief moment, roughly from 2008-2010, governments and central banks appeared to borrow from Keynes to save the global economy. The contributors, however, take the view that to see those stimulus measures as "Keynesian" is a misinterpretation. Rather, neoliberalism demonstrated considerable resiliency despite its responsibility for the deep and prolonged crisis. The "austerian" analysis of the crisis is--historical, ignores its deeper roots, and rests upon a triumph of discourse involving blame-shifting from the under-regulated private sector to public or sovereign debt--for which the public authorities are responsible."--